Durability performance of silica fume and fly ash-based concrete under short-term exposure to sulfate, chloride, and acidic groundwater: An experimental investigation - Azare, Ahmed Aliyu; Mohd Haziman, Wan Ibrahim; Ali Mangi, Sajjad; Sri Umniati, Baiq.; Putra Jaya, Ramadhansyah (Springer Nature, 2026)
Concrete structures susceptible to early deterioration through chemical attack, microstructural disruption, and degradation of strength are those exposed to sulfate, chloride, and acidic groundwater. Specimens (concrete) were exposed to determine the resistance of concrete to these chemicals, and were also partially replaced with silica fume and fly ash at a weight equivalent to the cement, in order to determine the optimum percentage of replacement. Although the addition of supplementary cementitious materials (SCMs), such as silica fume (SF) and fly ash (FA), is considered to enhance durability, the literature on the subject has been limited to single exposure environments, standard Portland cement systems, or long-term performance. High-strength self-compacting concrete (HSSCC) using ternary combinations of SF and FA in various aggressive exposure conditions and acidic groundwater has not been adequately studied in terms of its short-term durability response. The study gives a comparative experimental research of the short-term durability performance (28–90 days) of ternary blended HSSCC when exposed to sulfate, chloride, and acidic groundwater. The variation in compressive strength, change in mass, and damage indices were used to evaluate the durability performance and assess the sensitivity of degradation under varying chemical media. The findings suggest that the integrated use of SF and FA has a substantial positive impact on early-age resistance to chemical attack, due to the refinement of the pore structure, restriction of aggressive ion penetration, and reduction of strength loss compared to the control mix. The synergistic effect of the fast microfilling and pozzolanic activity of SF, combined with the slow, prolonged pozzolanic reaction of FA, has a significant impact on enhancing early durability in an aggressive environment. This research provides insight into the understanding of early-age degradation mechanisms of ternary blended HSSCC and offers a performancebased framework for understanding long-lasting operation in chemically aggressive groundwater and industrial conditions.